Effects of Exercise Aerobic Endurance Against Shooting Ability - Dinda zona fitri; Argantos . (Universitas Negeri Padang, 2019)
This study aims to determine the development of martial arts degree training, in improving athletes' achievements, it is expected that this research can contribute information for input for fostering achievement achievements. This research is a qualitative research using observation, interview and documentation data collection methods. The data analysis technique used is qualitative data analysis technique. The results of the study are: (1) The quality of the trainers at SATLAT SMAN 1 Batang Anai, Padang Pariaman Regency can be categorized as good, based on the results of data analysis conducted. (2) Sources of funding at SATLAT SMAN 1 Batang Anai, Padang Pariaman Regency are in accordance with Indonesian Law No. 3 of 2005 concerning the National Sports System, but are still categorized as not good, because funding at SATLAT SMAN 1 Batang Anai, Kabupaten Padang Pariaman only relies contributions from athletes. (3) Infrastructure facilities at SATLAT SMAN 1 Batang Anai, Padang Pariaman Regency are generally categorized as good, this can be seen from the adequate training equipment and training grounds.